Screening of crude extract from gills of male mud crabs (scylla serrata) - Tee, Yih Hou (2013)
Marine organisms had been found for the presence of various medical and pharmaceutical value. There are a lot of research and study being carried out on marine organism to extract the possible latent value within them, there are study on hepatopancreas, haemolymph, carapace, and even gills over the crustacean, and most of the study had detect many precious value such as antimicrobial, antifungal and antifouling properties. The purpose of this study is to determine whether gills of mud crabs reside antibacterial or antifouling property and determine the functional compounds. The book of gills from the male mud crabs were used for analysis. Book of gills were extracted through selected solvent (Methanol, acetone and ethyl acetate) to obtain the crude extracts. The crude extracts were later went through antibacterial and antifouling test to determine the presence of possible valuable bioactive compounds. The crude extracts were then followed by thin layer chromatography to determine the Rf value of the crudes and determine the polarity of the potential functional group present. Chromatography reagent of dragendorff and vanillin-sulfuric acid were used to determine the presence of certain functional group within the extracts. The Methanol crude performed best on the disc diffusion test and shown the highest inhibition width, later followed by ethyl acetate crude, but the acetone crude did not shown any inhibition towards the selected bacteria strains. For the antifouling properties, there are no significant antifouling activity being found for the all extracts. Through thin layer chromatography, there are alkaloid and possibly steroid functional group of bioactive compound within the gills extracts. The finding for the presence of antibacterial property in the gills of mud crabs can provide alternative antibiotic to mitigate the situation of antibacterial resistance issue that exaggerated day by day.